Salafis in Egypt's new politics: ideological adaptation or compromise? - Taufiq Radja Nurul Bahri (2016)
The Egyptian elections have thrown up an unexpected force in the Salafi Nour Party. Is it making an ideological shift or a pragmatic compromise?